Effects of the diet on seahorse (Hippocampus hippocampus) growth, body colour and biochemical composition. (7th November 2014) - Segade, Á.; Robaina, L.; Otero‐Ferrer, F.; García Romero, J.; Molina Domínguez, L.
Abstract: The short‐snouted seahorse ( Hippocampus hippocampus ) is a benthic fish that bases its survival on camouflage with the environment; therefore, both in wild and in captivity specimens, differences in coloration have been observed. This study was conducted to study the effect of five different diets, based on Artemia and frozen mysis, on fish survival, growth, skin colour parameters and biochemical composition. After 102 days of feeding different diets, no effect was observed on fish survival, growth, protein, ash or humidity content, except for colour changes on yellow and red fish. Differences on seahorse lipid and total carotenoids content were obtained in the experiment because of experimental diets. Fish eating Artemia showed the highest colour pattern response during the trial, with a maximum yellowness attained of 21. Additionally, a plateau of the skin colour expression for Artemia‐ feeding fish was reached on day 180. A reversion of the yellowish skin colour was determined after a change of diet.